Antibacterial Activity of Combination of Betel Leaf Extract and Star Fruit Using Hydroextraction Method - Tilarso, Dara Pranidya; Muadifah, Afidatul; Handaru, Windu; Pratiwi, Putri Indah; Khusna, Mursyidah Lathifatul; Tarigan, Indra Lasmana (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2022)
Antibacterial compounds are bioactive substances capable of inhibiting bacterial growth by disrupting the metabolism and cellular processes of pathogenic microorganisms. Natural plant-derived compounds have been widely explored for their antibacterial properties, with star fruit (Averrhoa bilimbi L.) and betel leaf (Piper betle) recognized for their potent antimicrobial effects. This study aimed to evaluate the antibacterial activity of a combination of star fruit and betel leaf extracts against Escherichia coli and Staphylococcus aureus, two clinically significant bacterial pathogens. The extraction process was performed using hydro-extraction at different temperatures (40°C, 50°C, 60°C, and 90°C) to determine the optimal conditions for bioactive compound yield. Antibacterial activity was assessed using the disc diffusion method, measuring inhibition zones to indicate bacterial susceptibility. The results demonstrated that the optimal inhibitory effect occurred at 50°C, producing an inhibition zone of 19.75 mm for Staphylococcus aureus and 11.75 mm for Escherichia coli. These findings suggest that temperature plays a critical role in maximizing the antibacterial potential of plant extracts. The study highlights the potential application of star fruit and betel leaf extracts as natural antibacterial agents, particularly against Gram-positive and Gram-negative bacteria. Further research is recommended to explore the mechanism of action, phytochemical composition, and potential synergy of these extracts in antimicrobial formulations.